Sintering densification behavior of molybdenum tungsten alloys - WU Zhou; WANG Na; WU Ji-na; ZHU Qi; XI Sha; ZHANG Xiao; ZHANG Tie-jun; AN Geng; ZHOU Sha; ZHANG Jun-li (Fenmo yejin jishu, 2021)
The shrinkage and densification behavior of Mo–30W alloys sintered by spark plasma sintering (SPS) and vacuum hot pressing sintering were studied by in-situ measurement method. The results show that, the Mo–30W alloys by SPS are mainly characterized by expansion below 1200 ℃, the shrinkage of the Mo–30W alloys begins strongly above 1200 ℃, and the shrinkage tends to stop above 1600 ℃; in the cooling stage, there is a strong shrinkage of the Mo–30W alloys, and the shrinkage basically stops when the temperature is close to room temperature. The relative density of Mo–30W alloys by SPS at 1600 ℃ is over 93%, which is better than that of 89.98% by vacuum hot pressing sintering at the same temperature.